THE EFFECTS OF RESTAURANT FOOD SERVICE APPLICATIONS PERCEPTION ON RESTAURANT REVISIT INTENTION - Virginia, Vania; Satyadi, Michael Ariel; Herng, Low Yeu; Yi, Tan Sin; Jahan, Khan Nusrat (International Journal Of Tourism, 2023)
The food service industry has increasingly adopted technology-based services, such as Food Service Application (FSA), to minimize physical contact and promote social distancing. FSA offers benefits for customers and businesses, such as saving time on the ordering process. A study was conducted using convenience sampling and an online questionnaire to collect 216 respondents. The data was analyzed using IBM Statistical Package for the Social Sciences (SPSS) software. The study aimed to examine the relationship between FSA features and customer perception and the relationship between consumer perception of FSA features and customer revisit intention. Results showed that FSA Features, FSA Responsiveness, FSA Reliability, and FSA Assurance positively correlated with FSA perception. FSA Responsiveness was found to be the most influential feature on FSA perception.